2003
DOI: 10.1136/jmg.40.11.e121
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary xanthinuria type II associated with mental delay, autism, cortical renal cysts, nephrocalcinosis, osteopenia, and hair and teeth defects

Abstract: No astract availabl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The first two disorders are clinically recognizable and distinct, while the latter is unlikely in the absence of gross disturbance of biochemical profile. Zannolli et al [2003] reported an 11-year-old boy with hereditary xanthinuria type II associated with nephrolithiasis and behavioral impairment, in which there is low plasma and urinary uric acid, and hematuria. This disorder was excluded from the patients in this report.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The first two disorders are clinically recognizable and distinct, while the latter is unlikely in the absence of gross disturbance of biochemical profile. Zannolli et al [2003] reported an 11-year-old boy with hereditary xanthinuria type II associated with nephrolithiasis and behavioral impairment, in which there is low plasma and urinary uric acid, and hematuria. This disorder was excluded from the patients in this report.…”
Section: Discussionmentioning
confidence: 97%
“…These conditions are typically associated with characteristic biochemical findings. Nephrocalcinosis with central nervous system or behavioral impairment may occur in Williams syndrome [Pober et al, 1993], Beckwith-Wiedmann syndrome [Goldman et al, 2003], and in xanthinuria type II [Zannolli et al, 2003]. We describe a possible new syndrome in which distal RTA with nephrocalcinosis accompany neurobehavioral dysfunction, short stature, and distinctive facial appearance in a consanguineous Arab family with four affected siblings.…”
Section: Introductionmentioning
confidence: 87%
“…AOX gene is located on 2q33 locus. [10] Clinically their manifestations are almost the same, and discrimination between these two types can be realized only with allopurinol loading test. Allopurinol is metabolized into oxypurinol with AOX enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Homologues of this gene were subsequently found to be mutated in xanthinuria type II in both bovine and human [11,12]. Consistent with the more general role of mal in the formation of molybdoenzymes, xanthinuria type II is characterized by combined xanthine dehydrogenase and aldehyde oxidase deficiency, and can produce more severe phenotypes than xanthine dehydrogenase deficiency alone [13]. In addition, metabolic variations between two wild‐type strains Oregon R (OR) and Canton S (CS), which are deemed to be genetically equivalent, and the Chocolate ( cho ) mutant, in which the genetic lesion is unidentified, were also studied.…”
Section: Introductionmentioning
confidence: 97%